The Brass Tacks Entrepreneur - Schell, Jim (New York Henry Holt, 1994)
A guide to starting a small business covers business plans, financing, employee selection, bankers, lawyers, consultants, quality, training, common mistakes, and keys to success
Keywords: Social change -- Social entrepreneurship -- Business